2019
DOI: 10.1016/j.sjbs.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with E. coli causing neonatal calf diarrhea

Abstract: Calf diarrhea is one of the major health challenges in cattle herds. The bacteriological examination of fecal samples collected from apparently healthy and diarrheic calves' revealed isolation of 26 E. coli isolates out of 56 calves with an incidence of 46.4%. Serogroups O1, O26, O44, O55, O115, O119, O125, O146, and O151 were identified from the collected fecal samples. Using PCR all isolates was positive for ompA gene species specific for E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 14 publications
4
24
2
3
Order By: Relevance
“…These results are agreeing with the findings reported in many studies (Joon and Kaura, 1993;Hussain et al, 2003;Wani et al, 2004;Osman et al, 2012). The serogroups O1, O115, O119, and O146 recovered in our study have also been showed in diarrheic calves (Mohammed et al, 2019). The serogroups O1 showed in our study have also been recovered in diarrheic calves (Wani et al, 2004 andBhat et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…These results are agreeing with the findings reported in many studies (Joon and Kaura, 1993;Hussain et al, 2003;Wani et al, 2004;Osman et al, 2012). The serogroups O1, O115, O119, and O146 recovered in our study have also been showed in diarrheic calves (Mohammed et al, 2019). The serogroups O1 showed in our study have also been recovered in diarrheic calves (Wani et al, 2004 andBhat et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…The problem of microbial resistance is growing by time and the outlook for the use of antimicrobial drugs in the future is still uncertain. Therefore, actions must be taken to face this problem and to introduce the antibacterial activity of medicinal plants ( Cowan, 1999 , Nostro et al, 2000 , Osman et al, 2013 , Osman et al, 2014a , Osman et al, 2014b , Osman et al, 2014c ; Wagdy et al, 2016; Abdel Halium et al, 2019 , Mohamed et al, 2019 , Ibrahim et al, 2019 ). In this study the antibacterial findings of Psidium guajava extract at different concentration have that able to inhibit the growth of S. aureus , Pasteruella multocida and Mycoplasma gallisepticum that correlated with the findings of Concalves et al (2008) , who studied guava extracts against food born pathogen and spoilage bacteria that due to the phenolic components which make them effective against the tested microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…count (Table 2). They are considered the most common pathogens in bovine milk, that increase newborn calves mortality rate, as well as, it could be dangerous for humans if raw colostrum has been consumed without thermal treatment (Stewart et al, 2005;Alegbeleye et al, 2018;Mohammed et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Contaminated colostrum, however, may contain pathogens and can be an infectious disease transmitter, affecting morbidity and mortality rates of animals in the farms (Stewart et al, 2005;Morales-delaNuez et al, 2011;Mohammed et al, 2018). Bovine milk contains complex microbiota that affects quality and safety of the product.…”
Section: Introductionmentioning
confidence: 99%